Immigration and Electoral Outcomes: Evidence from the 2015 Refugee Inflow to Germany - Julia Bredtmann (Institute of Labor Economics (IZA), 2022)
This paper investigates the effects of local exposure to refugees on electoral outcomes in the 2016 state election in Germany. Based on quasi-random variation in the allocation of refugees across municipalities and unique data on refugee populations and their type of accommodation, I find that an increase in the population share of refugees increases the vote share of right-wing parties and decreases the vote share of the incumbent federal government parties. The electoral effects, however, are solely driven by refugees living in centralized accommodation, while no such effects are found for refugees living in decentralized accommodation. These findings have important implications for the design of public policies in handling future receptions of refugees, as they reveal that an earlier transfer of refugees from centralized to decentralized accommodation could attenuate a growing support for right-wing parties.
Keywords: D72; F22; J15; R23; 330; immigration; refugees; political economy; voting